Nonverbal emotional regulation in psychotherapy process according to an intersubjective perspective - Melani, Paolo <1971> (Alma Mater Studiorum - Università di Bologna, 2012)
In recent decades fascinating studies in developmental psychology, especially in infant research (for review see Lavelli, 2007) and recent discoveries in neuroscience (Welsh, et al, 2007; Siegel, 2001; Pally, 2007) have brought great interest to study the mode of sharing subjective experiences (affective states, intentions and attentional focus) in children and adults.It therefore appears today in the clinic is a growing consensus about the fact that the psychological disorder can be read as a deficit in intersubjective processes of affect regulation (see Benecke C. et al 2005; psychodynamic Diagnostic Manual-PDM, 2006) leading many authors to assume the centrality of affect regulation in the construction of the psychotherapeutic process of change (just to name a few Tronick, Greenberg, Stern, Sander, Fonagy, Beebe, Philippot, Rimé etc..). As previously stated, this study has led us to hypothesize that the long process of therapy is to assist with the sessions continue, a growing "emotional attunement" between the communication styles of both patient and therapist. And also to speculate that this synchronization can represent the existence of a significant positive correlation between the increased level of "emotional synchronization" and increased capacity for regulation of emotions by the patient.The research results despite the limitations of small sample showed encouraging results about the verification of the existence of an increasing degree of attunement between therapist and patient long psychotherapy sessions and also showed a good degree of positive correlation between the increase the latter construct and emotional regulation through the implicit mode of expression and nonverbal communication.